2022
DOI: 10.1021/acs.energyfuels.2c01113
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Thickness Dependence upon Ge-Sensitized Thermal Cells

Abstract: The semiconductor-sensitized thermal cell (STC) is an attractive technology that used low-temperature heat (<200 °C). STC generates electricity by the redox reactions of electrolyte ions with thermally excited carriers in semiconductors. The most valuable feature of the STC is that, after power generation was completed, the performance recovers by leaving the cell in the heat source. However, the reason for this restore has been unclear. In this study, the recovery phenomenon was investigated with the viewpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Hwang’s group presented the influence of monolayered RuO 2 nanosheets and Co 2+ ion linkers on improving electrocatalytic H 2 evolution of MoS 2 nanoflowers . Nakajima and Matsushita investigated the recovery phenomenon of the semiconductor-sensitized thermal cell and found that the cell with the thinnest thickness and smallest quantity of electrolyte discharged for the longest time …”
Section: Electrocatalysismentioning
confidence: 99%
“…Hwang’s group presented the influence of monolayered RuO 2 nanosheets and Co 2+ ion linkers on improving electrocatalytic H 2 evolution of MoS 2 nanoflowers . Nakajima and Matsushita investigated the recovery phenomenon of the semiconductor-sensitized thermal cell and found that the cell with the thinnest thickness and smallest quantity of electrolyte discharged for the longest time …”
Section: Electrocatalysismentioning
confidence: 99%
“…53 Recently, an N-(4-methoxyphenyl)-9,9-dimethyl-9H-fluoren-2-amine-functionalized poly(N-vinylcarbazole) dopant free polymer has been reported for high charge mobility in PSSC with 18.44% efficiency. 54 Oligo(ethylene glycol)-functionalized PTAA-based PSSC yielded a solar conversion efficiency of 22.26%. 55 The functional reactivity and rapid redox behavior of the nitroxide radicals cause expansion of the charge diffusion, electrode reaction kinetics, and photovoltaic reaction.…”
Section: Introduction and Backgroundsmentioning
confidence: 99%
“…The solar efficiency of P5NH (donor–acceptor)-based PSSC was reported as 18.1%, comparatively higher than P3HT (15.50%) and P25NH . Recently, an N -(4-methoxyphenyl)-9,9-dimethyl-9 H -fluoren-2-amine-functionalized poly­( N -vinylcarbazole) dopant free polymer has been reported for high charge mobility in PSSC with 18.44% efficiency . Oligo­(ethylene glycol)-functionalized PTAA-based PSSC yielded a solar conversion efficiency of 22.26% .…”
Section: Introduction and Backgroundsmentioning
confidence: 99%
“…Ge is one of the promising semiconductors that has been used for diodes, detectors, and energy conversion materials. (5)(6)(7) Polyimide substrates have been used for the production of electronic devices and small lightweight wearable devices because polyimide has high mechanical strength, dimensional stability, wear resistance, heat resistance, and chemical resistance. Polyimide is a polymer with imide bonds in the main chain and is synthesized using polyamic acid, which is a product of the reaction between tetracarboxylic acid anhydride and oxydianiline upon high-temperature heating.…”
Section: Introductionmentioning
confidence: 99%